Using guard interval signal to improve tone reservation method for peak‐to‐average power ratio reduction in orthogonal frequency division multiplexing systems. Issue 6 (1st August 2015) - Sohtsinda, Hermann; Bachir, Smail; Perrine, Clency; Duvanaud, Claude
Abstract : Although orthogonal frequency division multiplexing is adopted by many standards in wireless communication systems, it generates high peak fluctuations which are affected by radio frequency circuit non‐linearities, reducing the power efficiency and the network quality of service. In recent years, tone‐reservation using null subcarriers (TRNS) scheme has been proposed to reduce the level of these fluctuations, measured by the peak‐to‐average power ratio (PAPR). However, TRNS performances only depend on the available number of null subcarriers in the current standards. In this study, a new scheme to improve TRNS performances by including the samples of the guard interval signal within the parameters of the optimisation algorithm is proposed, allowing higher PAPR reduction gain and requiring no side information. Simulations under the wireless local area network IEEE 802.11a standard show that the new method does not violate the specified spectrum mask and achieves a higher PAPR reduction gain compared to TRNS method. Also, the evaluation of bit error rate and error vector magnitude under additive white Gaussian noise and Rayleigh fading channels shows a comparable level of the quality of communication between the two schemes.